Pengujian Antimikroba, Kelembaban, Tingkat Iritasi, dan Tinggi Busa pada Hand Soap Berbasis Minyak Jelantah dan Zaitun: Testing of Antimicrobial, Humidity, Irritation, and Height of Foam for Hand Soap Based of Used Cooking and Olive Oils - Syamsul Bakhri Mapparessa; Zakir Sabara; Andi Suryanto; Lisa; Tri Isra Wahyu Lestari (KOVALEN: Jurnal Riset Kimia, 2023)
Used cooking oil can disturb health if used continues, and the waste can damage of environment if discarded, therefore prevention is needed through processing (recycling) of used cooking oil to economic products, for example, hand soap. This research was the manufacture of hand soap using the waste of cooking oil, olive oil, and KOH as raw materials. The aim is to determine formulations of raw materials on good hand soap on organoleptic tests, pH, microbial inhibitory zones, humidity and irritation levels, and foam height. The formulations between used cooking oil and olive oil are F1 (125 g and 125 g), F2 (150 g and 100 g), F3 (175 g and 75 g), and F4 (200 g and 50 g). This study begins with the manufacture of hand soap using the experimental method, continued by testing the inhibiting zone of growth of Propionibacterium acne bacteria, moisture content, irritation level, foam height through descriptive tests with analytical observational, organoleptic, and pH. Results are all formulas of hand soap have strong effectiveness in inhibiting microbe growth, distinctive organoleptic, moisturizing, and anti-irritation. The foam height has met with SNI 06-4085-1996, however, the pH value has larger than the pH of SNI 06-4085-1966. The best hand soap preparation is Formula 1 (F1) because it has a pH value that is close to the pH value of SNI.